Continuum and discrete models of dislocation pile-ups. II. Pile-up of screw dislocations at the interface in a bimetallic solid - Voskoboinikov, R; Chapman, S; Ockendon, J (2007)
The methodology developed in the precursor to this paper is used to find the positions of n screw dislocations in a pile-up against an interface bonding two crystalline solids. The pile-up is caused by a constant applied stress and, as n , the dislocations are located with sufficient accuracy to predict the large but finite stress distribution at the interface. Such a prediction is impossible using a conventional continuum dislocation density.